2022
DOI: 10.3390/ijms23105646
|View full text |Cite
|
Sign up to set email alerts
|

Association between Decreased ITGA7 Levels and Increased Muscle α-Synuclein in an MPTP-Induced Mouse Model of Parkinson’s Disease

Abstract: Parkinson's disease (PD) is a neurodegenerative disease characterized by the loss of dopaminergic neurons in the substantia nigra (SN), reducing dopaminergic levels in the striatum and affecting motor control. Herein, we investigated the potential relationship between integrin α7 (ITGA7) and α-synuclein (α-syn) in the muscle of methyl-4-phenyl-1,2,3,6 tetrahydropyridine (MPTP)-induced mice and C2C12 cells. To characterize the pathology of PD, we examined the expression of tyrosine hydroxylase (TH) in the SN of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Among them, the integrin subunit alpha 7 (ITGA7) protein is mainly expressed in skeletal muscle and myocardium, and it may be involved in differentiation and migration during myogenesis. The defect of this gene is associated with congenital myopathy [39][40][41]. In addition, studies have found that ITGA7 plays an important role in the early stages of osteogenesis by upregulating the PI3K-AKT signaling pathway [39].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the integrin subunit alpha 7 (ITGA7) protein is mainly expressed in skeletal muscle and myocardium, and it may be involved in differentiation and migration during myogenesis. The defect of this gene is associated with congenital myopathy [39][40][41]. In addition, studies have found that ITGA7 plays an important role in the early stages of osteogenesis by upregulating the PI3K-AKT signaling pathway [39].…”
Section: Discussionmentioning
confidence: 99%
“…5 Thus, low levels of α-syn expression and correct localization at the postsynaptic region of the NMJ is important for normal muscle function and glucose transport, but high levels and mislocalization of α-syn can lead to muscle wasting and dysfunction. Increased α-syn protein expression was detected in muscles from the methyl-4-phenyl-1,2,3,6tetrahydropyridine (MPTP) mouse model of PD 8 and treatment of C2C12 muscle cells with 1-methyl-4phenylpyridinium increased α-syn protein expression. 9 Furthermore, α-syn expression was identified in extracellular medium from isolated skeletal muscles from aged rats.…”
Section: The Role Of α-Synuclein and Tau In Skeletal Muscle α-Synucle...mentioning
confidence: 99%
“…Starting from an initial review of the impairment in the synthesis of dopamine and serotonin due to mutations in the ddc coding for aromatic amino acid decarboxylase (AADC) [1] that lead to severe pathological conditions of infantile parkinsonism, the main focus is on neurodegeneration and Parkinson's disease (PD) as well as the regulation of epilepsy and neuroendocrine cells. Han [2,3] and Seo [4] studied the expression levels of various genes coding for tyrosine hydroxylase, serine/arginine-rich protein-specific kinase 3, and integrin α7 with respect to α-synuclein in SH-SY5Y and C2C12 cells as well as in a PD mouse model. Interestingly, all these proteins were less expressed in cells and the muscles of the mouse model, while α-synuclein expression was increased.…”
mentioning
confidence: 99%